PENERAPAN DESIGN THIKING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN BANGUN RUANG KELAS V - Rafly Andhika; Lutfi Hamdani Maula; Iis Nurasiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore how the implementation of the Design Thinking approach can enhance students' critical thinking skills in learning three-dimensional geometry in Grade V at SDN Cipanas. The research was driven by initial observations showing that many students struggled to grasp mathematical concepts, particularly in solid shapes, due to learning methods that relied heavily on memorization and lacked opportunities for higher-order thinking. The research employed a Classroom Action Research (CAR) method, conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through critical thinking tests and observation sheets that monitored student and teacher activities throughout the learning process. The findings revealed a steady improvement in students' critical thinking abilities. The average score increased from 49.6 in the pre-cycle phase to 66.7 in cycle I, and reached 81.2 by the end of cycle II. The percentage of students who met the minimum passing criteria rose significantly, from 10% in the pre-cycle to 86% in the final cycle. These results indicate that the Design Thinking approach fosters a more engaging and meaningful learning environment, encouraging students to think logically, creatively, and reflectively. Thus, this approach is recommended as an innovative teaching strategy to strengthen 21st-century skills in primary school mathematics education.